Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja terhadap Kinerja Pegawai Melalui Motivasi Kerja pada Sekretariat Daerah Kabupaten Tanjung Jabung Timur - Eko Sumantri; Pantun Bukit; Sudirman Sudirman (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to describe leadership style, work environment, work motivation and employee performance at the Regional Secretariat of East Tanjung Jabung Regency and analyze the influence of leadership style and work environment through work motivation on employee performance at the Regional Secretariat of East Tanjung Jabung Regency. The method used in this research is descriptive verification and quantitative methods. The object of research in this study is the influence of leadership style and work environment through work motivation on employee performance at the Regional Secretariat of East Tanjung Jabung Regency. This research uses path analysis method. Based on the description of leadership style, work environment, work motivation and employee performance at the Regional Secretariat of East Tanjung Jabung Regency that leadership style is included in the "good" category, the work environment is included in the "good" category, employee motivation is included in the "high" category, while employee performance is included in the "good" category. Based on the results of path analysis, the total influence of Leadership Style (X1) and Work Environment (X2) on Work Motivation (Y) is 91.2%. Then in total the influence of Leadership Style (X1) and Work Environment (X2) on Performance (Z) is 84.5%. Work Motivation has a positive and significant effect of 65.3% on employee performance at the Regional Secretariat of East Tanjung Jabung Regency. While the direct influence of Leadership Style and Work Environment together through Work Motivation on the total influence of Leadership Style (X1) and Work Environment (X2) on Performance (Z) through Work Motivation is 59.2%.